1996
DOI: 10.1200/jco.1996.14.1.257
|View full text |Cite
|
Sign up to set email alerts
|

Predicting etoposide toxicity: relationship to organ function and protein binding.

Abstract: Increased hematologic toxicity after etoposide in patients with abnormal organ function is mediated by an increase in free etoposide AUC. A reduction in dose is clearly indicated in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…Our data con®rm the ®ndings of Joel, who studied the pharmacokinetics and dynamics of i.v. etoposide in patients with small cell lung cancer and found that protein binding and renal function in¯uence the toxicity of etoposide, by affecting the free drug exposure [11]. Although the model con®rms the importance of free drug exposure for toxicity, there remains a substantial interpatient variability in pharmacodynamics not explained by patient characteristics such as the performance status, pretreatment with chemotherapy or baseline white blood cell counts.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our data con®rm the ®ndings of Joel, who studied the pharmacokinetics and dynamics of i.v. etoposide in patients with small cell lung cancer and found that protein binding and renal function in¯uence the toxicity of etoposide, by affecting the free drug exposure [11]. Although the model con®rms the importance of free drug exposure for toxicity, there remains a substantial interpatient variability in pharmacodynamics not explained by patient characteristics such as the performance status, pretreatment with chemotherapy or baseline white blood cell counts.…”
Section: Discussionmentioning
confidence: 98%
“…For etoposide, a topoisomerase II inhibitor, haematological toxicity is closely related to unbound drug exposure [10,11]. Joel et al [12] hypothesized the existence of a therapeutic window, but further studies are needed to better de®ne the therapeutic concentration or exposure to etoposide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies have demonstrated that mild-to-moderate liver dysfunction (bilirubin Ͼ1-2 mg/dl) does not affect etoposide PKs, but severe impairment (not clearly defined) can contribute to greater toxicity (myelosuppression, mucositis) because of reduced hepatobiliary metabolism [16 -19]. In addition, albumin levels have been identified as important, with a higher fraction of unbound etoposide being directly related to high serum bilirubin and low albumin, which can lead to greater hematological toxicity [20]. However, the pharmacologic effects may not be altered at all in those patients with hepatic dysfunction and hypoalbuminemia resulting from greater renal clearance [21].…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%
“…Numerous attempts to define a priori dosage adjustments of etoposide has been made and predominantly such dosing algorithms base dosage on renal function [8,9] or hepatic function [10][11][12]. A more refined way to adjust dosing has been the application of a maximum a posteriori (MAP) Bayesian guided dosing, utilizing knowledge of the population distribution of the pharmacokinetic parameters for the drug [13][14][15].…”
Section: Introductionmentioning
confidence: 99%